GENERASI PEDULI BUDAYA MADURA GUNA MENINGKATKAN DAYA SAING PRODUK BATIK TANJUNG BUMI DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN - Siti Nur Aisyah (Kompetensi (Competence : Journal of Management Studies), 2017)
Indonesia had beenentered an era of Asean Economic Community (AEC), undeniablecultural developments in particular Batik kept experience a shift even as the rapid flow of western culture that entered the general public make lifestyle changed in particularfor young people. Culture is a flexible and dynamic, needed a way to optimize the culture within preservation. Batik industry needs to be built in the empowerment of the community, especially the younger generation. In the era of both economic Asean community's love for culture has begun to fade and slowly began to leave his real identity. Madura societies has a personality with the religious values and traditional values that are still awake until I today. The cultural values that exist to make local wisdom as the driving force of development if carried out in this region. So that they can provide added value (value added) for the preservation of batik industry. District of Tanjung Bumi great potential in mapping the products according to their potentials. The hope through this optimum would be able to preserve the cultural or local wisdom Batik is through industrialization, played by youth. Gelidara (Gerakan Peduli Budaya Madura) Youth portrayed by subdistrict Tanjung Bumi youth Organization. Youth Organization (Karang Taruna) has a strategic role in the empowerment of youth and is expected to optimize the industrialization of batik Tanjung Bumi. In addition to preserving Batik Tanjung Bumi youth Organization (Karang Taruna) culture youth can also increase their own income or the income of the government and new innovations that can be applied through the resulting product.